FRAMING BERITA MEDIA ONLINE TERHADAP FENOMENA SHOLAT IDUL FITRI TAHUN 1444 H DI PONDOK PESANTREN AL-ZAYTUN - Misroji; Nada Shofiyyah Hafizhah (STAI DI AL-HIKMAH, 2023)
This research aims to find out the correct way to perform the Eid al-Fitr prayer according to what Allah taught the Prophet and how Panji Gumilang responded, who acted as the initiator of the Eid al-Fitr prayer which changed the rules in Islam and to find out the differences in framing between the online media Kompas.com and Republika.co.id regarding news about Eid al-Fitr 1444 H prayers at the Al-Zaytun Islamic boarding school. This research uses a descriptive qualitative approach, namely a type of research that aims to provide a systematic and careful description of the actual facts and characteristics of a certain population. Using Robert N Entman's framing analysis tool to analyze research objects. This research data collection uses 2 techniques, namely, observation and documentation. By observing and copying all the news related to the Eid al-Fitr prayer case at the Al-Zaytun Islamic Boarding School, which was published on Kompas.com in June 2023 and on Republika.co.id in April 2023. The results of this research show differences in reporting regarding Eid al-Fitr 1444 H prayers at the Al-Zaytun Islamic Boarding School on the online media. Kompas.com frames the news by focusing on general sources, while Republika.co.id chooses sources who are Islamic-minded. Another difference relates to the packaging of Kompas.com titles which tend to use standard language such as